Incidence and influential factors in pulp necrosis and periapical pathosis following indirect restorations: a systematic review and meta-analysis - Kholod Khalil Al-Manei; Shuruq Alzaidi; Ghadah Almalki; Khaled Al-Manei; Nabeel Almotairy (BMC, 2023)
Abstract Background Restoring vital teeth with indirect restorations may threaten dental pulp integrity. However, the incidence of and influential factors on pulp necrosis and periapical pathosis in such teeth are still unknown. Therefore, this systematic review and meta-analysis aimed to investigate the incidence of and influential factors on pulp necrosis and periapical pathosis of vital teeth following indirect restorations. Methods The search was conducted in five databases, using MEDLINE via PubMed, Web of Science, EMBASE, CINAHL, and Cochrane Library. Eligible clinical trials and cohort studies were included. The risk of bias was assessed using Joanna Briggs Institute's critical appraisal tool and Newcastle-Ottawa Scale. The overall incidences of pulp necrosis and periapical pathosis following indirect restorations were calculated using a random effects model. Subgroup meta-analyses were also performed to determine the potential influencing factors for pulp necrosis and periapical pathosis. The certainty of the evidence was assessed using the GRADE tool. Results A total of 5,814 studies were identified, of which 37 were included in the meta-analysis. The overall incidences of pulp necrosis and periapical pathosis following indirect restorations were determined to be 5.02% and 3.63%, respectively. All studies were assessed as having a moderate-low risk of bias. The incidence of pulp necrosis following indirect restorations increased when the pulp status was objectively assessed (thermal/electrical testing). The presence of pre-operative caries or restorations, treatment of anterior teeth, temporization for more than two weeks, and cementation with eugenol-free temporary cement, all increased this incidence. Final impression with polyether and permanent cementation with glass ionomer cement both increased the incidence of pulp necrosis. Longer follow-up periods (> 10 years) and treatment provided by undergraduate students or general practitioners were also factors that increased this incidence. On the other hand, the incidence of periapical pathosis increased when teeth were restored with fixed partial dentures, the bone level was < 35%, and the follow-up was > 10 years. The certainty of the evidence overall was assessed as low. Conclusions Although the incidences of pulp necrosis and periapical pathosis following indirect restorations remain low, many factors affect these incidences that should thus be considered when planning indirect restorations on vital teeth. Database registration PROSPERO (CRD42020218378).